Calidad de vida y derecho al reconocimiento en la vejez = Quality of life and right to be recognized in old age - Dulcey-Ruiz, Elisa (Oñati Socio-Legal Series, 2011)
From the standpoint of admitting the relativity, complexity and multiple meanings of the concepts quality of life, recognition and old age, this paper refers to these concepts and their relationships, taking into account, as a framework, the challenge to construct inclusive societies: for women and men of all ages and conditions. Based on this, quality of life during the entire life span, and specifically in old age (when someone has lived most) is considered as a result of the interaction of biological, historical, cultural and social variables. Besides, subjective and objective, individual and collective, synchronic and diachronic aspects are highlighted. According to that, the right to be recognized implies considering the persons' dignity and their value as human beings that are capable of pronouncing themselves, deciding and participating in society, both as contributors to and beneficiaries of development, in conditions of equality. In concluding, reference is made to the need to take into account and assume the heterogeneity that involve the aging and old age, as well as the urgency of overcoming stereotypes, prejudices and discrimination in this regard.